Antiviral and Immunostimulant Activities of Andrographis paniculata - . CHURIYAH; OLIVIA BUNGA PONGTULURAN; ELRADE ROFAANI; . TARWADI (HAYATI Journal of Biosciences, 2015)
Andrographis paniculata (Burm. f.) Nees is a medicinal plant which was reported to have anti HIV, anti pathogenic bacteria and immunoregulatory activities. The research purpose was to investigate the activity of Andrographis paniculata ethanol extract as antiviral and immunostimulant. A. paniculata leaves oven-dried, then grinded and macerated with ethanol 90%, and the extract then analyzed using High Performance Liquid Chromatography (HPLC) to determine the content of active compounds andrographolide. The antiviral activity of the extract was determined by observing its ability on inhibiting virus load in A549 cells transfected with Simian Retro Virus (SRV) by Real Time – Polymerase Chain Reaction (RT-PCR) analysis. The immunostimulant activity of extract was determined by its ability to induce lymphocytes cell proliferation using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Our result indicated that the A. paniculata ethanol extract inhibited the SRV virus titer similar to the positive control Lamivudine, and it was not toxic to the A459 cell line. Furthermore, low concentration (1 μg/mL) of A. paniculata extract could stimulated lymphocyte cell proliferation about 38% compared to the control lymphocyte cell without any treatment.